Exploring the Abnormal Modulation of the Autonomic Systems during Nasal Flow Limitation in Upper Airway Resistance Syndrome by Hilbert–Huang Transform - Lin, Chen; Lo, Men-Tzung; Guilleminault, Christian (Frontiers in Medicine, 2017)
Patients with nasal flow limitation and upper airway resistance syndrome (UARS) during sleep can present with low blood pressure and disturbing symptoms associated with hypervagotony. We hypothesized that the dynamic changes of the autonomic system related to inspiratory flow limitation can be quantified by the developed analytic technique applied on beat-to-beat heart rate (RR intervals) and finger photoplethysmography (PPG). Method A breath-by-breath investigation based on the Hilbert-Huang Transform was performed to explore autonomic nervous system changes observed during inspiratory flow limitation. Autonomic status was quantified from beat-to-beat heart rate analysis by high frequency (RRHF; 0.15-0.4 Hz), low frequency (RRLF; 0.04-0.15 Hz) and LF/HF ratio of each respiratory cycle. Based on respiratory-related mechanisms contained in the PPG signal, we further quantified the respiratory-related oscillations (PPGres). Based on esophageal pressure and nasal flow measurements, each respiratory cycle was identified and breathing patterns were classified into one of four groups: normal, inspiratory flow limitation cycles without increased effort [FL(-)], minimal inspiratory flow limitation with effort, and inspiratory flow limitation cycles with increased effort [FL(+)]. The resulting quantitative parameters of the identified cycles were calculated. Results 49 UARS patients (12 males; aged 26.8±5.8 years) with AHI 3.1±1.5 per hour and 9 aged matched control subjects (3 males; aged 27.8±4.0 years) with AHI 0.8±1.1 per hour were recruited. Compared to the control group, hyper-activation of the parasympathetic system was noted during stage 2 NREM sleep by RRHF (27.8±18.2 vs 22.5±11.12, p<0.05) in 49 UARS patients. Analysis of the different classifications of respiratory cycles indicated that during ‘high” (increased) respiratory efforts, the RRHF and PPGres were significantly higher compared to “normal cycle” and “FL(-)” groups. The RRLF/RRHF (an index of sympathetic activity) was significantly lower in the “FL(+)” group (1.66±0.80) than in the “normal cycle” (1.93±0.97, p<0.05) and “FL(-)” groups (2.01±1.01, p<0.05). Conclusion The proposed algorithm allows quantifying the temporal changes of specific mechanisms of the autonomic system on breath-by-breath basis. With no or very limited impact on oxygen saturation, the hyperactivation of parasympathetic system in associated with inspiratory flow limitation or increased respiratory efforts during stage 2 NREM sleep has been presented in this study.